New tools help assess and enhance Africa’s water–energy systems - Harou, Julien; Tahavori, Mohammad Amin; Hafeez, Mohsin (CGIAR, 2023)
African governments, policymakers, and other stakeholders in the water and energy sectors face a balancing act. On the one hand, they must sustainably maximize water and energy access for widespread and often remote populations; on the other, they are racing to mitigate and adapt to the escalating effects of climate change. Their job is made harder by a siloed approach to decision-making, which remains one of one of the biggest challenges to delivering effective, sustainable solutions across the water–energy–food–ecosystems (WEFE) nexus.